Making Connections: Communication through the Ages - Meadow, Charles T. (Rowman & Littlefield Publishers, 2002)
Meadow takes us on a Cook's tour of communication technologies across time—the alphabet and moveable type printing, cave drawings and carrier pigeons, telephones, television and, of course, the Internet. In each case, Meadow shows how these (and other devices) are connected to each other, even as they serve to make connections between people. Part One discusses the basics of communications, while Part Two delves into telecommunications before the days of steam and electricity. Part Three offers insight into steam, electricity, and internal combustion energy and how they revolutionized society. Communication is the key to a productive world. For those dazzled by the pace of change in the technology or McLuhan's unorthodox but brilliant insights, Meadow's casual style and pace provide the perfect antidote.